Application of Adaptive Algorithms on Ultrasound Imaging - Maryam Idrees; Hafiza Faheela; Faizan Ahsan Wali (Engineering Proceedings, 2023)
Ultrasound, also known as ultrasonography, plays a major role in the medical imaging field. Ultrasound images are inevitably prone to different kinds of noise and speckle during their acquisition. Adaptive filters show the best performance in removing noise and speckles from images. In this paper, we compared the least mean square algorithm, the quaternion least mean square algorithm, and the normalized least mean square algorithm for ultrasound image processing. It was demonstrated that NLMS displayed the best performance of these algorithms. The results are provided in order to illustrate the performance of algorithms.